2018
DOI: 10.4143/crt.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

Risky Lifestyle Behaviors among Gastric Cancer Survivors Compared with Matched Non-cancer Controls: Results from Baseline Result of Community Based Cohort Study

Abstract: PurposeThis study investigated the prevalence of smoking, drinking, and physical inactivity and the associated factors of these behaviors in gastric cancer survivors.Materials and MethodsThe baseline data from the nationwide cohort study was used. Four hundred thirty-seven gastric cancer survivors who survived ≥ 2 years from diagnosis and reported completion of treatment were matched with 4,370 controls according to age, sex, education, and household income.ResultsThe prevalence rates of current smoking and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…The result of the association between increments in age and the lower likelihood of current drinking in this study was also observed in other study [16]. The associations between employment, self-rated health status, and higher physical inactivity as well as the correlation between comorbidities and lower physical inactivity were comparable with a previous study on gastric cancer survivors [27]. Long working hours could be a reason for the increased physical inactivity in employees.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of the association between increments in age and the lower likelihood of current drinking in this study was also observed in other study [16]. The associations between employment, self-rated health status, and higher physical inactivity as well as the correlation between comorbidities and lower physical inactivity were comparable with a previous study on gastric cancer survivors [27]. Long working hours could be a reason for the increased physical inactivity in employees.…”
Section: Discussionsupporting
confidence: 90%
“…While it is known that females have better health-related lifestyles than males in the general population and cancer survivors [26,27], interestingly, studies show that the prevalence of smoking is higher in female cancer survivors than non-cancer subjects with significant sex-drinking/smoking interaction [17]. However, in this study, female thyroid cancer survivors showed healthier behaviors than male thyroid cancer survivors in terms of both smoking and drinking but did not show differences in physical activity.…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, the studies published thus far scarcely give a clear overview of the food components of the evaluated diets. For that reason, there is a need to further characterize the diet quality among GI cancer survivors [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst evidence is limited and inconsistent, there are a number of studies suggesting that cancer survivors make positive changes to health behaviours after a cancer diagnosis [9,10,11,12], and cancer survivors have healthier lifestyle behaviours than those who are cancer-free [13,14,15]. These findings emanate the notion that the period after a cancer diagnosis be considered as a “teachable moment”, whereby cancer survivors may be receptive to lifestyle change messages and may be more motivated to make healthy behaviour changes [16,17].…”
Section: Introductionmentioning
confidence: 99%